HV interval in calcific aortic stenosis. Relation to left ventricular function and effect of valve replacement. Issue 1 (July 1984) - Rasmussen, K; Thomsen, P E; Bagger, J P
Abstract : Intracardiac electrography and 24 hour ambulatory electrocardiographic monitoring were carried out in 20 patients with calcific aortic stenosis (mean pressure gradient 86 mm Hg) to investigate (a) the role of bradycardia and tachycardia in the pathogenesis of syncope in aortic stenosis, (b) the relation between haemodynamic data and electrophysiological abnormalities, and (c) whether valve replacement corrects electrophysiological abnormalities. Intracardiac electrograms showed impaired sinus node function in five patients and a prolonged HV interval (greater than or equal to 50 ms) in 11 but there was no difference in the findings of 13 patients with syncope and seven without. Ambulatory monitoring showed short pauses in three patients and brief episodes of tachycardia in four, but there was no difference in the findings of patients with and without syncope. The HV interval correlated inversely with the left ventricular ejection fraction, whereas no correlation was found between the HV interval and the pressure gradient. Nine patients were re-evaluated 15 months after aortic valve replacement. No change was found in sinus node function, but the HV interval had increased by 7.8 ms. It is concluded that in calcific aortic stenosis neither bradycardia nor tachycardia is shown to be a frequent cause of syncope, a prolonged HV interval is a frequent finding and further prolongation occurs after valve replacement, and contractility and conductivity appear to deteriorate in parallel.